Dynamics of funding liquidity and risk-taking: Evidence from commercial banks - Faisal Abbas; Shoaib Ali; Imran Yousaf; Wing Keung Wong (Journal of Risk and Financial Management, 2021)
The purpose of this study is to investigate the impact of funding liquidity risk on the banks' risk-taking behavior. To test the hypotheses, we apply the two-step system GMM technique on US commercial banks data from 2002 to 2018. We find that funding liquidity increases the banks' risk-taking of US commercial banks. Furthermore, banks with higher deposits are less likely to face a funding shortage, and bank managers' aggressive risk-taking activity is less likely to be monitored. Our findings infer that increases in bank funding liquidity increase both risk-weighted assets and liquidity creation, and deposit insurance creates a moral risk issue for banks taking excessive risks in response to deposit rises. The relationship between funding liquidity and the banks' risk-taking varies with their capitalization and market conditions; the impact of funding liquidity on risk-taking is pronounced for well-capitalized banks and the Global Financial Crisis 2007. Our tests are robust for the usage of alternate proxy of funding liquidity and by controlling economic conditions. The findings of this study have implications for regulators to develop guidelines for the level of liquidity and risk-taking of commercial banks.
Keywords: G21; G01; G18; 330; funding liquidity; liquidity creations; risk-weighted assets; Z-scores